Official methods of analysis of AOAC international (Oxford University Press, Inc., 2023)
The Official Methods of Analysis of AOAC INTERNATIONAL is a comprehensive collection of approximately 2,500 validated chemical and microbiological methods and consensus standards related to food, drugs, agriculture, and the environment. This latest edition provides the essential information for the analytical scientists working in relevant fields of chemistry.